Manipulation of Asymmetric Transmission in Planar Chiral Nanostructures by Anisotropic Loss. Issue 7 (17th June 2013) - Li, Zhaofeng; Gokkavas, Mutlu; Ozbay, Ekmel
<x xml:space="preserve">Abstract</x> Planar chiral structures may provide asymmetric transmission for circularly polarized optical waves at normal incidence if the structures are anisotropic and lossy, but the role of loss has not yet been clarified. Here, a typical planar chiral structure is studied, and the mechanism of asymmetric transmission is analyzed. It is demonstrated for the first time that asymmetric transmission can be manipulated by changing the anisotropy of loss. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>